2017
DOI: 10.1177/0002716217707176
|View full text |Cite
|
Sign up to set email alerts
|

Schools at the Rural-Urban Boundary: Blurring the Divide?

Abstract: Schools mirror the communities in which they are located. Research on school inequality across the rural-urban spectrum tends to focus on the contrast between urban, suburban, and rural schools and glosses over the variation within these areas as well as the similarities between them. To address this gap and provide a richer description of the spatial distribution of educational inequality, we examine the school composition, achievement, and resources of all U.S. elementary schools in 2010–2011. We apply stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…We define “nearest” by using GIS software to find the nearest metropolitan principal city to every rural school. Rural schools are then considered to be part of that nearest principal city’s metro-plus zone (see Burdick-Will and Logan 2017). …”
Section: Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We define “nearest” by using GIS software to find the nearest metropolitan principal city to every rural school. Rural schools are then considered to be part of that nearest principal city’s metro-plus zone (see Burdick-Will and Logan 2017). …”
Section: Methods Of Analysismentioning
confidence: 99%
“…In related research (Burdick-Will and Logan 2017) we compared city, suburban, and rural schools. We found that inner-suburban schools are somewhat more like central city schools, while schools on the suburban periphery are more like rural schools.…”
Section: Segregation and School Disparitiesmentioning
confidence: 99%
“…To illustrate, although public schools in the same district or municipality are financed from the same source and governed by the same policies, they vary in terms of racial/ethnic composition, wealth concentration, student performance, school and class size, teacher-to-student ratio, school-level administrative organization, etc. (Burdick-Will & Logan, 2017). Even when schools share a campus and a mascot, they tend to have distinct populations with unique internal cultures (Godsey, 2015).…”
Section: Differences Within School Districts and Municipalitiesmentioning
confidence: 99%
“…This scholarship is varied in approach, wide-ranging in focus, and embedded in a variety of subfields and disciplines (see, e.g., Lichter & Ziliak, 2017). For example, economists, political geographers, sociologists, and legal scholars have examined diverse topics such as the relationship between geographical space and income/wealth inequality (Glasmeier, 2018), urban poverty (Soja, 2010), educational inequality (Burdick-Will & Logan, 2017), and access to indigent criminal defense (Pruitt & Colgan, 2010). While not all of these studies explicitly situate themselves in the tradition of spatial inequality research, common across these studies are efforts to “examine how and why markers of stratification, such as economic well-being and access to resources as well as other inequalities related to race/ethnicity, class, gender, age, and other statuses, vary and intersect across territories” (Lobao, Hooks, & Tickmayer, 2007, p. 3).…”
Section: Theoretical Frameworkmentioning
confidence: 99%